Research on cloud manufacturing service architecture and consensus algorithm based on blockchain technology - Weijin JIANG; Wenying ZHOU; En LI; Tiantian LUO; Ying YANG (物联网学报)
With the deep integration of information technology and manufacturing, the networking of manufacturing transactions has become an inevitable trend.Cloud manufacturing services can realize cross-supplier transactions that are not limited by geographical space, but in the process of transaction, there are problems such as difficulty in guaranteeing the trust of both parties and leakage of privacy.In order to solve the above problems, a cloud manufacturing service platform architecture based on a dual-chain model was proposed, which stores user data and transaction data in separate chains, and adopts a practical Byzantine fault tolerance (PBFT) consensus algorithm to solve the problem of data synchronization between blocks.However, traditional PBFT consensus algorithm has bottlenecks in storage and consensus efficiency, and is not suitable for large-scale manufacturing platforms.Therefore, further research on the PBFT consensus algorithm was carried out.The election process was optimized and the consensus protocol process of the consensus cluster was improved by combining the EigenTrust model and the quality of service (QoS), and then give the manufacturing resource rent-seeking and matching steps.Analysis and simulation experiments show that this research effectively improves the reliability of PBFT consensus nodes, improves the operating efficiency of the platform and the speed of block consensus, and saves data storage space.